Interchanging interaction between heritage and technical in the local architectural practice - Abdul-Ahadd, Enas Salim; Mahdi, Rana Mazin (Iraqi Journal of Architecture and Planning, 2018)
An architectural local practice facing a crisis associated with losing the local intermediated feature for local heritage and rapid development, which is a feature of the current era.The research focuses on the case of intermediation in expression between heritage privacy (as it cannot be denied the whole heritage or accept the whole) and the expression of the spirit of the times and new techniques to ensure the continuity of architectural output achieved in time and space thus The research problem absented of equilibrium expressionist architectural output arises between the ancient and the modern..Proceeding from the need Establishment the successes of architectural based inherited to attributes of the positive image associated with sense and collective memory and without verbatim copying or repeat boring of its components may represent objective of this research offering mechanics to harness developments technological era to achieve the balancing expressive with local heritage to ensure re-line local architectural back on track right through emphasize in their possession on elements and traditional forms of obstetric capacity for new forms stating the design process and architectural practice as a whole. To achieve the target research had to belimiteda steps which represent as: - Û±Clarify the role of the architectural heritage of the container to the external forces of change (represented by contemporary technology) to confront the case of alienation. - Û²highlight the technical for the development of architectural production to ensure continuity and contact with the former - Û³Recovery mechanisms to modernize and applied to the heritage elements of Baghdad heritage an elected for the application to provide alternatives to represent architectural designer formal possibilities to connect with the old in a new modern kind of case the revival of traditional elements.